Studies on the application of bio-carbon dioxide as controlled atmosphere on pest management in wheat grain storage. (January 2022) - Kumar, Himanshu; Vijay, Virendra K.; Subbarao, Paruchuri M.V.; Chandra, Ram
Abstract: The study evaluated the viability of purified waste gas called bio-CO2 (CO2 ≥ 98%, CH4 ≤ 2.0%, v/v), which is a byproduct from a compressed biogas (CBG) plant, as a new source of CO2 for control atmosphere for wheat grain storage. The findings were compared with the use of pure CO2 on mortality of Rhyzopertha dominica adults, seed germination, and nutritional quality of wheat grain for two and six months storage periods. Fifteen tapered plastic bottles of 1 L storage volume were taken for grain storage. Insect mortality of 100% was found in 1, 3, and 5 days using bio-CO2 and 4, 6, and 8 days with pure CO2 at 80, 60, and 40% concentration, respectively. In control grain infested with R. dominica, the adult insect triplicated in six weeks, 3.9 times in two months, and 10.4 times in 6 months storage. There were no significant differences (p > 0.05) observed in seed weight stored for two and six months under the bio-CO2 fumigation. Whereas, seed weight loss of about 5.03 ± 0.8% in control without infestation and 17.25 ± 1.2% in grain infested with R. dominica were reported over two months storage. Similarly, no weight loss during controlled atmosphere treatment, 12.66 ± 0.34% in control, and 27.42 ± 0.96% with R. dominica were found for six months storage period. The seed germination was significantly affected at 80% CO2 using both the controlled atmosphere for grain stored for six months. The major nutrient contents remained non-significant (p > 0.05) under both the fumigants. Whereas, carbohydrate content was significantly reduced (p < 0.05), and protein content was increased in control without infestation and grain infested with R. dominica . Highlights: Stored product pest management. Efficacy of bio-CO2 as a controlled atmosphere in pest control. Effect of bio-CO2 on nutritional quality of wheat grain. Purging efficiency. Adult Rhyzopertha dominica mortality.